1999
DOI: 10.1002/(sici)1097-4628(19990801)73:5<795::aid-app19>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aggressive environments on composite properties

Abstract: Glass-fiber-reinforced epoxy and unsaturated polyester (UPE) composites were fabricated from diglycidyl ether of bisphenol-A (DGEBA) using 10% diethyl triamine (DETA) as a hardener and unsaturated polyester (UPE) using 1.5% each of methyl ethyl ketone peroxide (MEKP) and cobalt naphthanate as a catalyst and an accelerator, respectively. The fabricated composites were exposed to different aggressive environments, such as heat, water ageing, lubricating oil, fuel, and seawater. The exposed specimens were charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…This was attributed to interfacial degradation and also to microstructural changes in rice husk that reduced its efficiency in acting as a reinforcer. Siddaramiah et al9 exposed glass‐fiber‐reinforced epoxy and unsaturated polyester composites to different aggressive environments, including heat aging, water aging, lubricating oil, fuel, and seawater and obtained a marginal increase in properties with heat aging but a reduction in properties in the other exposed systems.…”
Section: Introductionmentioning
confidence: 99%
“…This was attributed to interfacial degradation and also to microstructural changes in rice husk that reduced its efficiency in acting as a reinforcer. Siddaramiah et al9 exposed glass‐fiber‐reinforced epoxy and unsaturated polyester composites to different aggressive environments, including heat aging, water aging, lubricating oil, fuel, and seawater and obtained a marginal increase in properties with heat aging but a reduction in properties in the other exposed systems.…”
Section: Introductionmentioning
confidence: 99%
“…In service, structural metal joints, polymer coatings, and fiber-reinforced composites are often operating in humid and warm conditions, which leads to hydrothermal aging of the bond. 1,2 The hydrothermal aging behavior of epoxy systems is often focused because they are widely used in structural applications. For epoxies adhesives, many studies are reported in literature concerning the degradation of the joint strength during a variety of hydrothermal loading.…”
Section: Introductionmentioning
confidence: 99%
“…Styrene is the crosslinking agent in unsaturated polyesters. Several authors have suggested that some unreacted resin and catalyst that did not take part in the polymerization reaction are still present [9][10][11]42]. It is well known that three types of reactions are inherent in unsatured polyesters: curing polymerization of polyester vinyl groups, polyester and styrene CBC bond polymerization, and styrene homopolymerization [42][43][44][45][46].…”
Section: Degradation Modelmentioning
confidence: 99%
“…Wiles [53,54] suggested a mixed mechanism of thermal and photolytic oxidation in polymers containing carbonyl groups in the form of acid, ester, aldehyde, ketone, amide, or peroxide. Glass fiber reinforced polyester composites continuously exposed to a temperature of 50°C do not lose their mechanical characteristics in the absence of solar radiation, as shown in a number of references [9][10][11]30]. The prevalent mechanism during composite irradiation is photoluminic, while thermal aging would produce higher losses due to fiber-matrix interface degradation [12,13,55].…”
Section: Degradation Modelmentioning
confidence: 99%
See 1 more Smart Citation